Liriodenine, an aporphine alkaloid from Enicosanthellum pulchrum, inhibits proliferation of human ovarian cancer cells through induction of apoptosis via the mitochondrial signaling pathway and blocking cell cycle progression - Nordin N; Majid NA; Hashim NM; Rahman MA; Hassan Z; Ali HM (Dove Medical Press, 2015)
Noraziah Nordin,1 Nazia Abdul Majid,2 Najihah Mohd Hashim,1 Mashitoh Abd Rahman,1 Zalila Hassan,3 Hapipah Mohd Ali3 1Department of Pharmacy, Faculty of Medicine, 2Institute of Biological Sciences, 3Department of Chemistry, Faculty of Science, University of Malaya, Kuala Lumpur, Malaysia Abstract: Enicosanthellum pulchrum is a tropical plant from Malaysia and belongs to the Annonaceae family. This plant is rich in isoquinoline alkaloids. In the present study, liriodenine, an isoquinoline alkaloid, was examined as a potential anticancer agent, particularly in ovarian cancer. Liriodenine was isolated by preparative high-performance liquid chromatography. Cell viability was performed to determine the cytotoxicity, whilst the detection of morphological changes was carried out by acridine orange/propidium iodide assay. Initial and late apoptosis was examined by Annexin V-fluorescein isothiocyanate and DNA laddering assays, respectively. The involvement of pathways was detected via caspase-3, caspase-8, and caspase-9 analyses. Confirmation of pathways was further performed in mitochondria using a cytotoxicity 3 assay. Apoptosis was confirmed at the protein level, including Bax, Bcl-2, and survivin, while interruption of the cell cycle was used for final validation of apoptosis. The result showed that liriodenine inhibits proliferation of CAOV-3 cells at 37.3 µM after 24 hours of exposure. Changes in cell morphology were detected by the presence of cell membrane blebbing, chromatin condensation, and formation of apoptotic bodies. Early apoptosis was observed by Annexin V-fluorescein isothiocyanate bound to the cell membrane as early as 24 hours. Liriodenine activated the intrinsic pathway by induction of caspase-3 and caspase-9. Involvement of the intrinsic pathway in the mitochondria could be seen, with a significant increase in mitochondrial permeability and cytochrome c release, whereas the mitochondrial membrane potential was decreased. DNA fragmentation occurred at 72 hours upon exposure to liriodenine. The presence of DNA fragmentation indicates the CAOV-3 cells undergo late apoptosis or final stage of apoptosis. Confirmation of apoptosis at the protein level showed overexpression of Bax and suppression of Bcl-2 and survivin. Liriodenine inhibits progression of the CAOV-3 cell cycle in S phase. These findings indicate that liriodenine could be considered as a promising anticancer agent. Keywords: Enicosanthellum pulchrum, liriodenine, ovarian cancer, CAOV-3, apoptosis